Expansao das lavouras de soja e trigo no Estado de São Paulo - Sanchez, M. C. (My University, 1981)
Shows the viability of using the Trend Surface Analysis (TSA) in studies of the distribution of items of geographical interest in time and space; tests comparatively the techniques of cartographic representation conventionally used in TSA. It follows that the TSA offers more resources for analyses of the spatial items behaviour than the techniques commonly employed for the same purpose.- English summary
The expansion of the soybean and wheat crops in the state of São Paulo, Brazil